Growth, carbon assimilation and biochemical changes of oil palm seedlings (Elaeis guineensis Jacq.) in climate change factors with potassium fertilisation - Tuan Mohd Razali, Tuan Syaripah Najihah (2021)
The demand for palm oil is expected to increase due to the increase in world population. However, climate change poses significant challenges to the production of oil palm as its output can be directly affected by abiotic stress, especially water and temperature stress. Potassium (K) is a crucial element in oil palm plantation as it is directly involved in the crop physiological processes. Thus, this research was designed to determine how the use of the evapotranspiration replacement (ER) method and potassium fertiliser could be used to alleviate water and heat stress in oil palm seedlings. In the first experiment, four irrigation regimes [100% ER (well-watered), 75% ER (moderate water stress), 50% ER (high water stress), and 25% ER (severe water stress)] were used to investigate the effect of different water stress regimes on the physiology of 4-months old oil palm seedlings. Results showed that severe water stress decreased vegetative plant growth, plant water status, leaf gas exchange, water use efficiency (WUE), and fv/fm (maximum efficiency of photosystem II), but the malondialdehyde (MDA) and proline levels of oil palm seedlings were increased. In the second experiment, three levels of potassium rates (K1, K2, and K3) with five times applications (170, 340, and 510 kg KCl ha−1), (480, 960, and 1440 kg KCl ha−1), (170, 340, and 510 kg KCl ha−1), (960, 1920, and 2880 KCl kg ha−1), and (960, 1920, and 2880 kg KCl ha−1) under three different levels of water stress (100% ER, 75% and 25% ER) were exposed on oil palm seedlings to identify the best rate of potassium fertiliser under water stress application and to understand the interaction between drought impacts and potassium application on oil palm seedlings. The result revealed that water stress hampered the growth of oil palm seedlings. As potassium fertiliser rates increased, no significant differences in the physiology of the seedlings were observed except for height, net photosynthesis, and intercellular CO2 (Ci). However, the biochemical properties (proline, soluble sugars, and phenolics) of oil palm seedling increased by 50%, 60%, and 55% while MDA decreased by 40% compared to control when the application of K was doubled. Yet, there were no significant differences by applying double rate and triple rate of K. There was also an interaction between different water treatment levels and the rate of potassium fertiliser on the height, Ci and flavonoid level of oil palm seedlings. In the third experiment, three types of potassium fertiliser (KCl; Potassium chloride, K2SO4; Potassium sulphate and KNO3: Potassium nitrate) with a double rate of K under three levels of water stress (100% ER, 75% ER, and 25% ER) were exposed to oil palm seedlings to investigate the influence of potassium source in minimizing water stress effects in this crop. It was found that as the level of water reduced, the RGR (relative growth rate), LAR (leaf area ratio), LWR (leaf weight ratio), and SLA (specific leaf area) of oil palm seedlings reduced, but the value of R:S (root: shoot ratio) improved. The result also revealed that K2SO4 increased the leaf gas exchange and fv/fm as well as reducing the leaf temperature compared to KCl and KNO3. There was an interaction between water stress and the source of K on respiration rate and electrolyte leakage. K2SO4 also reduced the biochemical properties of oil palm seedlings. In the last experiment, the study was designed to investigate the effect of elevated temperature on the physiology of oil palm seedlings, to examine the combination of heat and water stress as well as to explore the potential of potassium fertiliser in alleviating these stresses. Oil palm seedlings were treated with six regimes: A (well-watered + control amount of KCl + 30°C), B (well-watered + control amount of KCl + 32°C), C (moderate water stress + double rate of K2SO4 + 30°C), D (moderate water stress + double rate of K2SO4 + 32°C), E (severe water stress + double rate of KNO3 + 30°C) and F (severe water stress + double rate of KNO3 + 32°C). The results showed heat stress decreased vegetative plant growth, plant water status, and increased leaf temperature. The effects were exacerbated by the combination of water stress. However, there was no significant effect of high temperature on the leaf gas exchange, WUE, fv/fm, SPAD chlorophyll value, and biochemical properties of the palms. The level of MDA, proline, soluble sugar, and lipid peroxidation only greatly increased under severe water stress. The present study suggests that only the growth of oil palms seedlings is sensitive to the 2°C rise, but not leaf gas exchange and biochemical attributes. Potassium fertiliser can play a protective role during moderate water stress under ambient temperature, thus supplying 75% water from soil field capacity, and doubling K2SO4 on oil palm seedlings under water scarcity is recommended. From this project, it can be concluded that the application of the evapotranspiration replacement method and potassium fertiliser were able to alleviate the abiotic stress in oil palm seedlings.